A Study on Consumer Perception towards Mutual Fund Investment of Retail Investors in Odisha (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2018)
Paper aims at studying the perception of investors towards mutual fund investment. The study is  based on a sample of 380 respondents chosen using convenience sampling to understand the  mutual fund buying behaviour of the individual investors. The paper determines various aspects  of mutual funds which are considered by investors while investing in mutual fund. Aspects like  reason for investment in mutual fund, preference of mutual fund are discussed.
Keywords: Mutual Funds; Fund Preference; Reason for Mutual Fund Investment